Incidencia de fugas en la red de abastecimiento de agua potable del Cantón Gonzalo Pizarro de la provincia de Sucumbíos. - Enriquez Chamba, Arianna Anahi (2025)
This study analyzes the incidence of leaks in the potable water supply network of the Gonzalo Pizarro canton, Sucumbíos Province. It focuses on Lumbaqui town, where approximately 80% of the population is served through the distribution network. Some households remain unconnected. Covering the period 2020–2024, the research combines a documentary review, operational analysis, and a water-balance assessment in accordance with IWA guidelines. The evaluation distinguishes between supplied and unaccounted-for water and, subsequently, between real and apparent losses. A field-macrometering campaign was conducted over a 10-month period. There were daily measurements during the first three months and monthly readings thereafter. This revealed a high Index of Uncontrolled Water (IANC): an annual average of 69.18% in 2020, with a slight reduction to 67.85% in 2024. These values are well above reference values, which recommend systems remain below 30%. The results show that accumulated real losses are high. Increases in injected flow do not improve the efficiency of the supply system, indicating a structural problem and resulting in economic losses. Overall performance reaches only 30.30%, which is rated as “unacceptable” because it is below 50%. An integrated plan is proposed that includes hydraulic sectorization, active pressure control, prioritized renewal of critical sections, macro- and micrometering, leak detection, and commercial regularization. Implementing this plan would reduce physical and economic losses and improve the service's sustainability.